2019
DOI: 10.1038/s41598-019-50439-y
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of memory retrieval for internal mentation

Abstract: Daily life situations often require people to remember internal mentation, such as their future plans or interpretations of events. Little is known, however, about the principles that govern memory for thoughts experienced during real-world events. In particular, it remains unknown whether factors that structure the retrieval of external stimuli also apply to thought recall, and whether some thought features affect their accessibility in memory. To examine these questions, we asked participants to undertake a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…Indeed, research has shown that periods of stability or gradual change in contextual features (e.g., one's surroundings and internal states) makes temporally proximal experiences to cohere with one another in memory (Howard, 2017;Polyn & Cutler, 2017), whereas contextual changes create separations in memory (i.e., event boundaries) that lead to distinct representational units (Clewett & Davachi, 2017;DuBrow et al, 2017;Radvansky & Zacks, 2017). While this organizational role of contextual states has been mainly evidenced using laboratory stimuli (i.e., word lists), recent studies have shown that the recall dynamics of real-world events follow similar principles (e.g., a temporal contiguity effect) (Diamond & Levine, 2020;Stawarczyk & D'Argembeau, 2019). Thus, contextual stability may contribute to the integration of information into meaningful experience units, whereas contextual shifts may be used as transition points to skip segments of past experience when remembering the unfolding of events:…”
Section: Principles That Structure the Organization Of Experience Unitsmentioning
confidence: 99%
“…Indeed, research has shown that periods of stability or gradual change in contextual features (e.g., one's surroundings and internal states) makes temporally proximal experiences to cohere with one another in memory (Howard, 2017;Polyn & Cutler, 2017), whereas contextual changes create separations in memory (i.e., event boundaries) that lead to distinct representational units (Clewett & Davachi, 2017;DuBrow et al, 2017;Radvansky & Zacks, 2017). While this organizational role of contextual states has been mainly evidenced using laboratory stimuli (i.e., word lists), recent studies have shown that the recall dynamics of real-world events follow similar principles (e.g., a temporal contiguity effect) (Diamond & Levine, 2020;Stawarczyk & D'Argembeau, 2019). Thus, contextual stability may contribute to the integration of information into meaningful experience units, whereas contextual shifts may be used as transition points to skip segments of past experience when remembering the unfolding of events:…”
Section: Principles That Structure the Organization Of Experience Unitsmentioning
confidence: 99%
“…Helstrup and Magnussen (2001) instructed participants to remember landmarks positioned along a route to a frequently visited vacation destination, with participants self-reporting more vivid memories for landmarks positioned towards the start and end of the route. Finally, Stawarczyk and D'Argembeau (2019) instructed participants to recall thoughts experienced during a 25 min walk. Memory was better for thoughts encountered at the start and end of the walk, with these thoughts arguably functioning as internal landmarks encountered during the walk.…”
Section: Introductionmentioning
confidence: 99%
“…The serial-position effects were described for the first time by Hermann Ebbinghaus ( Ebbinghaus et al., 1885/1913 ) and they state that the memory recall of an element varies as a function of its position inside the sequence. In the context of episodic memory, primacy and recency effects (the first ones or the last ones present higher recall) have been reported in different contexts such as TV ads ( Terry, 2005 ; Li, 2009 ), chronological memories ( Roediger and Crowder, 1976 ), parking locations ( Da Costa Pinto and Baddeley, 1991 ), music ( Overstreet and Healy, 2011 ) or internal mentation ( Stawarczyk & D’Argembeau, 2019 ). However, rates of recall are really low in the long-term, so studying how serial-position effects will affect pure episodic memories in the long-term is challenging.…”
Section: Introductionmentioning
confidence: 99%